2019
DOI: 10.3389/fbioe.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Extremophiles: Biotechnological Alternative to Crop Productivity in Saline Soils

Abstract: Salinization of soils is one of the main sources of soil degradation worldwide, particularly in arid and semiarid ecosystems. High salinity results in osmotic stress and it can negatively impact plant grow and survival. Some plant species, however, can tolerate salinity by accumulating osmolytes like proline and maintaining low Na + concentrations inside the cells. Another mechanism of saline stress tolerance is the association with symbiotic microorganism, an alternative that can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 100 publications
2
38
0
Order By: Relevance
“…The two fungal endophytes originally isolated from Antarctic plants, Penicillium chrysogenum and Penicillium brevicompactum, had previously been found responsible for increasing yield under water shortage and salinity conditions in lettuce 7,11 . Besides improving plant physiological parameters (A max and WUE), fungal endophytes also promoted the accumulation of the amino acid proline 7 , an osmotic molecule that has been previously suggested to mediate symbiont-conferred plant tolerance to water deficit 55,56 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two fungal endophytes originally isolated from Antarctic plants, Penicillium chrysogenum and Penicillium brevicompactum, had previously been found responsible for increasing yield under water shortage and salinity conditions in lettuce 7,11 . Besides improving plant physiological parameters (A max and WUE), fungal endophytes also promoted the accumulation of the amino acid proline 7 , an osmotic molecule that has been previously suggested to mediate symbiont-conferred plant tolerance to water deficit 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Under such scenarios, the physiological and biochemical functions of both wild and cultivated plant species are impaired causing severe yield losses 59 . Although it still needs to be tested at real production scales, harnessing fungal endophyte symbionts of plants appears to be a suitable strategy not only for improving crop yields but also for the design of environmentally friendly agricultural strategies 5,6,11,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, comparative genomics studies suggested that these fungi display similar genomic content to their associated organism, as well as symbiosis-specific genes [105,106]. The endophytic fungi can influence the physiology of the host plant by protecting against pathogenic fungi [104,107,108], promoting plant growth [97,109,110], and aiding nutrient and water uptake [111]. Moreover, studies have demonstrated the positive impacts of plant-endophyte associations in maintaining ecological balance and their potential biotechnological applications.…”
Section: Perspectives In Environment and Agriculturementioning
confidence: 99%